Structure, Composition, and Diversity of Dry Tropical Forest Types in the Sisimeni Sanam Forest Area, Kupang Regency, East Nusa Tenggara Province - Dako, Fransiskus Xaverius Dako; Flora Evalina Ina Kleruk; Kristianto Wibison So; Blasius Paga; Yudhistira A.N.R Ora (Talenta Publisher, 2025)
Sisimeni Sanam Forest Area is a tropical dry forest area on Timor Island that plays an important role in life, such as maintaining and preserving soil fertility, being the lungs of the world, being a place for living things to live, being a source of biodiversity, regulating water management, and preventing the dangers of flooding and erosion. Data and information regarding the ecology of vegetation in this forest are still limited. This study aims to determine the structure, composition, and diversity of vegetation types in the Sisimeni Sanam Forest Area. The method used is a systematic sampling method using a double rectangular plot with a plot size of 20 x 20 m (trees), 10 x 10 m (poles), 5 x 5 m (sapling), and 2 x 2 m (seedlings and understorey). The results of the study showed that the types of vegetation found were 49 species grouped into 25 families. Cromolaena odorata has the highest relative density and frequency values at the seedling and understorey levels, while Tectona grandis (teak) dominates at the sapling, pole, and tree levels. The important value index at each growth level is in the high category with a value range of 200% - 300%. The value of the Species Diversity Index (H') in the Sisimeni Sanam Forest Area shows a number <1, meaning it is included in the low category. Forests with low species diversity values indicate that the forest area has experienced disturbance or forest damage caused by both nature and humans